A Mutation in Escherichia coli DNA Gyrase Conferring Quinolone Resistance Results in Sensitivity to Drugs Targeting Eukaryotic Topoisomerase II - Gruger, Thomas (American Society for Microbiology, 2004)
Fluoroquinolones are broad-spectrum antimicrobial agents that target type II topoisomerases. Many fluoroquinolones are highly specific for bacterial type II topoisomerases and act against both DNA gyrase and topoisomerase IV. In Escherichia coli, mutations causing quinolone resistance are often found in the gene that encodes the A subunit of DNA gyrase. One common site for resistance-conferring mutations alters Ser(83), and mutations to Leu or Trp result in high levels of resistance to fluoroquinolones. In the present study we demonstrate that the mutation of Ser(83) to Trp in DNA gyrase (Gyr(S83W)) also results in sensitivity to agents that are potent inhibitors of eukaryotic topoisomerase II but that are normally inactive against prokaryotic enzymes. Epipodophyllotoxins, such as etoposide, teniposide and amino-azatoxin, inhibited the DNA supercoiling activity of Gyr(S83W), and the enzyme caused elevated levels of DNA cleavage in the presence of these agents. The DNA sequence preference for Gyr(S83W)-induced cleavage sites in the presence of etoposide was similar to that seen with eukaryotic type II topoisomerases. Introduction of the Gyr(S83W) mutation in E. coli strain RFM443-242 by site-directed mutagenesis sensitized it to epipodophyllotoxins and amino-azatoxin. Our results demonstrate that sensitivity to agents that target topoisomerase II is conserved between prokaryotic and eukaryotic enzymes, suggesting that drug interaction domains are also well conserved and likely occur in domains important for the biochemical activities of the enzymes.